TAHAPAN MUSYAWARAH PERENCANAAN PEMBANGUNAN (MUSRENBANG) DI KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI TAHUN 2021 - Sri Rahma Yana; Isril ' (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research was carried out in Kuantan Mudik District, Kuantan Singingi Regency to find out several things. Kuantan Mudik District, which has 23 villages and its capital city, namely Lubuk Jambi, has a lot of natural and economic potential to advance regional development. This of course requires planning for the development of facilities and infrastructure from the government. This research uses qualitative research methods, using two data source methods, namely primary data and secondary data. Primary data was obtained using interviews and documentation. And Secondary Data was obtained using books, journals, theses, laws, Home Affairs, Regional Regulations, and also social media and official websites. The results of this research show that it is not yet fully effective. In implementing the stages, the sub-district has formed a team to organize the Musrenbang, held MusrenbangDes in all villages in the Kuantan Mudik sub-district, conducted a pre-district Musrenbang before the implementation of the Musrenbag at the sub-district level. Then in the evaluation section of plan implementation, of course the level of participation is very influential in implementing Musrenbang. However, the results of this research still contain several shortcomings, such as some participants who were unable to attend due to livelihood obstacles, and also many community proposals that were not fully accommodated. Keywords: Stages, Participation, Musrenbang.